Abh, AbrB3, and Spo0A play distinct regulatory roles during polymyxin synthesis in Paenibacillus polymyxa SC2 - Yanru Cui; Dongying Zhao; Kai Liu; Xiangui Mei; Shanshan Sun; Binghai Du; Yanqin Ding (Microbiology Spectrum, 2024)
ABSTRACT Polymyxins exhibit antibacterial activity against various gram-negative bacteria. However, the regulatory mechanisms of polymyxin synthesis remain unclear. Here, Abh, AbrB3, and Spo0A of Paenibacillus polymyxa SC2 were found to bind to P pmx via DNA pull-down and electromagnetic mobility shift assays. Oxford Cup and liquid chromatography-mass spectrometry assays showed that antibacterial activity and polymyxin production increased in the Δabh strain. Overexpression of abh and abrB3 significantly decreased the antibacterial activity and polymyxin production. The transcription of pmxA determined via quantitative reverse transcription-PCR supported these results. Moreover, the mutation and complementation of spo0A revealed that Spo0A was an activator of polymyxin synthesis. Spo0A could bind to the abh promoter to activate abh expression. Spo0A could bind to the abrB3 promoter to inhibit abrB3 transcription and mitigate the inhibitory effect of AbrB3 on abh transcription. IMPORTANCE Polymyxins are considered the last line of defense against multidrug-resistant bacteria. The regulatory mechanism of polymyxin synthesis is poorly studied in Paenibacillus polymyxa. In this study, we found that Abh and AbrB3 negatively regulated, whereas Spo0A positively regulated polymyxin synthesis in P. polymyxa SC2. In addition, a regulatory relationship between Abh, AbrB3, and Spo0A was revealed, which regulate polymyxin synthesis via multiple regulatory mechanisms in P. polymyxa.